Evaluation of the Association Between Different Face Forms and Gingival Tissue Phenotype - Arshad, Neha; Amin, Erum; Malik, Ahsan; Tariq, Qurat-Ul-Ain; Nasir, Zainab (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the association between gingival tissue phenotype and different vertical facial patterns. Study Design: Cross-sectional study. Place and Duration of Study: Department of Orthodontics, Armed Forces Institute of Dentistry, Combined Military Hospital, Rawalpindi Pakistan, from May 2021 to Nov 2022. Methodology: Sixty-nine patients with good periodontal health who had not yet begun orthodontic treatment were chosen. The gingival phenotype was evaluated clinically. Patient face type was evaluated on the basis of two angles: maxillomandibular plan angle (MMA) and cranial base to mandibular plan angle (SN-MP) on lateral cephalograms. Results: The age of subjects ranged from 16 to 34 years (mean age 20.3±4.9) with nearly equal number of males 33(47.8%) and females 36(52.2%) subjects. Gingival type was not found to be correlated with both gender as well as age (p>0.05). However, a significant correlation was seen between gingival and vertical facial types (p=0.01). A significant difference was also seen between the attached maxillary and mandibular gingival widths and the vertical facial types (p=0.005 and p=0.05, respectively). Conclusion: The hyperdivergent face form is associated with a thin gingival phenotype, and the hypodivergent face form is associated with a thick gingival biotype. The normodivergent face type had a higher frequency of thin gingival biotypes in the studied population.